Cytosine base modifications regulate DNA duplex stability and metabolism. Issue 22 (16th June 2021) - Rausch, Cathia; Zhang, Peng; Casas-Delucchi, Corella S; Daiß, Julia L; Engel, Christoph; Coster, Gideon; Hastert, Florian D; Weber, Patrick; Cardoso, M Cristina
Abstract: DNA base modifications diversify the genome and are essential players in development. Yet, their influence on DNA physical properties and the ensuing effects on genome metabolism are poorly understood. Here, we focus on the interplay of cytosine modifications and DNA processes. We show by a combination of in vitro reactions with well-defined protein compositions and conditions, and in vivo experiments within the complex networks of the cell that cytosine methylation stabilizes the DNA helix, increasing its melting temperature and reducing DNA helicase and RNA/DNA polymerase speed. Oxidation of methylated cytosine, however, reverts the duplex stabilizing and genome metabolic effects to the level of unmodified cytosine. We detect this effect with DNA replication and transcription proteins originating from different species, ranging from prokaryotic and viral to the eukaryotic yeast and mammalian proteins. Accordingly, lack of cytosine methylation increases replication fork speed by enhancing DNA helicase unwinding speed in cells. We further validate that this cannot simply be explained by altered global DNA decondensation, changes in histone marks or chromatin structure and accessibility. We propose that the variegated deposition of cytosine modifications along the genome regulates DNA helix stability, thereby providing an elementary mechanism for local fine-tuning of DNA metabolism.